'He wasn't nice to our country': Children's discourses about the 'glocalized' nature of political events in the Global North. Issue 2 (June 2022) - Barley, Ruth
The accessibility of new media combined with emerging patterns of migration are challenging current definitions of community as we see a shift from close-knit face-to-face interactions to more diverse 'glocalized' networks that defines community as a social rather than a spatial dimension. These changes mean that social connections, and fundamentally a person's sense of belonging, have moved beyond a local neighbourhood to depend upon global networks. This was the case for the children in the current longitudinal ethnographic study that followed one class in a diverse primary school in the north of England every 2 years from their Reception year to Year 6. This article draws upon data collected while the children were in Year 6, aged 10 to 11. It uncovers the range of linguistic and semiotic resources that the children used to communicate with their school peers about two recent political events in the Global North, namely, the United Kingdom's European Union (EU) Referendum in 2016 that has resulted in Brexit and the US Presidential Election in late 2016 and Donald Trump's Inauguration in early 2017. Unearthing the 'glocalized' discourses in the children's narratives, this article uncovers the connections that the children made between these political events and their nuclear family's experiences living in the United Kingdom and their extended family's experiences in their countries of origin. In providing an account of the children's discourses surrounding these political events, this article uncovers the ways in which sociopolitical events of global significance become meaningful for this group of children and reveals that the children understand the global as situated, constructed within specific contexts and influenced by local interpretations. As the children orientate themselves to media depictions of these events, their shifting perceptions of global politics alongside their intersecting experiences of racial, national and religious inequalities come to the fore in their peer interactions at school.